2014
DOI: 10.2147/ijn.s64794
|View full text |Cite
|
Sign up to set email alerts
|

The influence of bile salt on the chemotherapeutic response of docetaxel-loaded thermosensitive nanomicelles

Abstract: The primary aim of this work was to investigate the potential of bile salt, sodium taurocholate (NaTC), in improving the bioavailability and anti-tumor efficacy of docetaxel (DCT) upon rectal administration. Poloxamer-based nanomicelles with thermosensitive and mucoadhesive properties were prepared using the cold method. The optimized nanomicellar formulation was evaluated in terms of physicochemical and viscoelastic parameters. Nanomicelles containing bile salt maintained sufficient gelation strength (234×10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…These nanomicelles possessed sufficient viscoelastic properties to remain in the upper part of the rectum for the specified time. They enhanced the absorption of docetaxel across the rectal mucosa and improved its half-life and plasma concentration, resulting in a significant in vivo anti-tumor efficacy ( Kim et al, 2014 ).…”
Section: Pharmaceutical Formulations and Drug Delivery Systems Contaimentioning
confidence: 99%
“…These nanomicelles possessed sufficient viscoelastic properties to remain in the upper part of the rectum for the specified time. They enhanced the absorption of docetaxel across the rectal mucosa and improved its half-life and plasma concentration, resulting in a significant in vivo anti-tumor efficacy ( Kim et al, 2014 ).…”
Section: Pharmaceutical Formulations and Drug Delivery Systems Contaimentioning
confidence: 99%
“…Moreover, the pharmacokinetic results showed that NaTC was influential in improving the half-life and plasma level of DCT. Although the elevated plasma level of DCT from the bile salt group did not enhance the anti-tumor potential, DCT-loaded nanomicelles could reduce the drug-related side effects, such as hypersensitivity reactions and fluid retention, while retaining the potential anti-tumor efficacy in clinical subjects [88].…”
Section: Bile Salts As Absorption Enhancermentioning
confidence: 99%
“…Anti-tumor efficacy of DCT-loaded nanomicelles with and without NaTC after rectal administration [88]. * Significantly smaller than control group ( p < 0.01).…”
Section: Bile Salts As Absorption Enhancermentioning
confidence: 99%
“…Poorly soluble drugs can be made soluble within the hydrophobic core of the nanoparticles and effectively delivered [12]. Such nanoparticles exhibits important properties including excellent systemic stability, high loading capacity, and preserving the pharmacological property of encapsulated drugs [13].…”
Section: Introductionmentioning
confidence: 99%